Biologia reprodutiva de Tropidurus callathelys Harvey & Gutbertlet, 1998 e Tropidurus chromatops Harvey & Gutbertlet, 1998 duas espécies simpátricas mas distantemente relacionadas dentro de um mesmo gênero de lagartos neotropicais, (Squamata; Tropiduridae) - Roberto, Nathally Gabrielle Albuquerque (2022)
The reproductive biology of Neotropical reptiles is little explored in view of the information available on species from temperate zones. In this context, conspicuous heliophile lizard species comprise an open field for descriptive and comparative studies approaching potential reproductive adaptations of distinct populations submitted to variable environmental pressures. Nonetheless, sympatric lizards belonging to distantly related species might exhibit convergent reproductive strategies, since they are under the very same environmental constraints. Herein, we investigated the reproductive biology of two sympatric and distantly related lizard species of the genus Tropidurus (T. callathelys, of the T. spinulosus group, e T. chromatops, of the T. torquatus group), looking for features that could reflect local adaptations to ecological and climatic conditions, as well as for parameters associated with phylogenetic inheritance. Our work took place in the Serra Ricardo Franco State Park, vicinities of Vila Bela da Santíssima Trindade, Mato Grosso state, the only area where both species occur in Brazil. We structured the present study in two chapters to be assessed as independent products. Chapter 1 approaches the description and comparison of the reproductive cycles of both target species, searching for adaptive and phylogenetic factors that might account for the differences and similarities detected. Chapter 2 explores sexual dimorphism and the associated phenomena in both target species, detailing the main dimorphic secondary features and discussing the evolutionary significance of differences of size, coloration and behavior, calling attention to the reverse dichromatism that characterizes T. callathelys.